The data collection toolkit everything you need to organize, manage, and monitor classroom data - Golden, Cindy (Paul H. Brookes Publishing, 2018)
"This book provides quick and easy tips for data collection within the classroom. Behavioral Quik-Graphs provides quick and easy tips for data collection within the classroom. Special educators, administrators, and other paraprofessionals often view data collection as time-consuming and complex, but collecting data on behaviors, academic abilities, and Individualized Education Plans (IEPs) is a crucial procedure that shows the progress of individual students. A variety of reproducible forms and tools are available for immediate use in recording and analyzing classroom data. Data collection is a critical piece of an educator's job (not just in special education) and it can be very intimidating to a teacher. This accessible book will make data collection easy with realistic vignettes, diagrams and sample forms, and explanations written in clear language"...